2022
DOI: 10.3390/machines10040266
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Driven Lower Limb Exoskeleton Rehabilitation Robot Based on Anthropomorphic Design

Abstract: To help people with impairment of lower extremity movement regain the ability to stand and walk, and to enhance limb function, this study proposes an anthropomorphic design of an electrically driven, lower-limb exoskeleton rehabilitation robot. The angular range of the robot’s motion was determined according to the characteristics of the targeted lower-limb joints; the robot was given an active–passive anthropomorphic design with 12 degrees of freedom. The multi-degree-of-freedom hip exoskeleton, bionic artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In order to generalize the calculation of different motor parameters, one possible approach may be to create different levels in this model, and use a converter to unify the input data across devices. However, this approach would need to be validated for each device individually, for example, a current study tested their simulated model against a marker based system and found consistent results with regard to joint angles [ 106 ]. Furthermore, it has been shown that exoskeletons can also have a direct impact on motor performance (e.g., balance [ 107 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In order to generalize the calculation of different motor parameters, one possible approach may be to create different levels in this model, and use a converter to unify the input data across devices. However, this approach would need to be validated for each device individually, for example, a current study tested their simulated model against a marker based system and found consistent results with regard to joint angles [ 106 ]. Furthermore, it has been shown that exoskeletons can also have a direct impact on motor performance (e.g., balance [ 107 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Flexible exoskeleton robots can be said to combine all three of these aspects: eliminating the rigid frame of traditional exoskeletons, optimizing the actuation methods (often using motors, cords, and pneumatic drives) based on the use of lightweight materials [54][55][56][57][58], and allowing for good wearing comfort and safety and have become a rapidly developing feld of increasing importance in assistive, disability and rehabilitation training [59][60][61][62][63][64]. Furthermore, in terms of comfort, Gao et al [27] looked at bionic structures and human-robot coupling to improve the human-robot coupling of rehabilitation robot confgurations and the compatibility of movements, thus enhancing the comfort of human-robot interaction.…”
Section: Realization Of Light Weight and High Comfortmentioning
confidence: 99%
“…The importance of the Exoskeleton has increased recently as a result of the sharp rise in the number of older persons. This technology is mostly used to repair or improve people's capacity to walk or carry standard objects because lower-limb neurological injuries, hemiplegia, lower-limb weakness, and movement disorders are on the rise due to unhealthy lifestyles, traffic accidents, and sports injuries [19,20]. The majority of knee exoskeletons use this type of pin-joint, which has only one DOF and a fixed rotation axis, as their representation of the knee joint [21].…”
Section: Dynamic Model Of Exoskeleton Systemmentioning
confidence: 99%